In vitro antimicrobial activity of Cymbopogon citratus (lemongrass) extracts against selected foodborne pathogens - Zakuan, Zulfa; Chia, C. T.; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Microbial contamination in food system poses risk towards public health. The usage of synthetic and chemical preservatives to prevent the contamination has become a growing concern due to the presence of deleterious and harmful substances that can cause environment and health problems in prolonged exposure. Thus, there are needs to overcome this problem by using natural products as food preservatives. In this study, the antimicrobial activities of methanolic Cymbopogon citratus (lemongrass) extracts were tested against five foodborne pathogens, namely Bacillus cereus, Escherichia coli O157:H7, Klebsiella pneumoniae, Staphylococcus aureus and Candida albicans. The susceptibility test, minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) or minimum fungicidal concentration (MFC) were conducted using the broth microdilution techniques as described by Clinical and Laboratory Standard Institute (CLSI). C. citratus extract showed antimicrobial activity against all tested foodborne pathogens; B. cereus, E. coli O157:H7, K. pneumoniae, S. aureus and C. albicans with the inhibition zone of 12 mm, 7.5 mm, 11 mm, 10 mm and 9 mm, respectively. The MIC of C. citratus extract against B. cereus, E. coli O157:H7, K. pneumoniae, S. aureus and C. albicans was 0.08 mg/ml, 0.63 mg/ml, 0.04 mg/ml, 0.31 mg/ml, and 0.16 mg/ml, respectively, while the MBC or MFC was 1.25 mg/ml, 2.50 mg/ml, 2.50 mg/ml, 1.25 mg/ml and 1.25 mg/ml, respectively. Time-kill curves were determined to assess the correlation between MIC and bactericidal activity of C. citratus extract at concentrations ranging from 0× MIC to 4× MIC. The bactericidal endpoint for B. cereus, E. coli O157:H7, S. aureus and C. albicans was at 4× MIC after 2 h, 4× MIC after 2 h, 4× MIC after 30 min and 4× MIC after 4 h, respectively whereas K. pneumoniae was not completely killed after 4 hours of incubation at 4× MIC. The potent antimicrobial activity of C. citratus extract may support its usage as natural antimicrobial agent.